2017
DOI: 10.1007/s12011-017-1083-2
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Extraction as Novel Approach to Compare 12 Medicinal Plants From Kenya Regarding Their Potential to Release Chromium, Manganese, Copper, and Zinc

Abstract: This study is focusing on a novel approach to screen a large number of medicinal plants from Kenya regarding their contents and availability of selected metals potentially relevant for treatment of diabetes patients. For this purpose, total levels of zinc, chromium, manganese, and copper were determined by flame atomic absorption spectrometry and inductively coupled plasma mass spectrometry as well as BCR sequential extraction to fractionate the elemental species in anti-diabetic medicinal plants collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
2
8
1
Order By: Relevance
“…This increases the plant safety as low amounts of As, Cd, Tl and Pb elements are absorbed. The results are contrary to those we reported for Zn, Mn, Cr and Cu in the sequential extraction as novel approach to compare 12 medicinal plants from Kenya regarding their potential to release chromium, manganese, copper and zinc (Mogwasi et al 2018). The low molecular mass species enhanced the absorption of the therapeutic elements while the existence of the toxic elements in large molecular weight species means less amounts are absorbed, lowering their toxicity.…”
Section: Ultra Ltration Of As CD Tl and Pb In Medicinal Plantscontrasting
confidence: 99%
See 3 more Smart Citations
“…This increases the plant safety as low amounts of As, Cd, Tl and Pb elements are absorbed. The results are contrary to those we reported for Zn, Mn, Cr and Cu in the sequential extraction as novel approach to compare 12 medicinal plants from Kenya regarding their potential to release chromium, manganese, copper and zinc (Mogwasi et al 2018). The low molecular mass species enhanced the absorption of the therapeutic elements while the existence of the toxic elements in large molecular weight species means less amounts are absorbed, lowering their toxicity.…”
Section: Ultra Ltration Of As CD Tl and Pb In Medicinal Plantscontrasting
confidence: 99%
“…The details on herbalist recruitment in Manga and Borabu sub-counties were as described in our previous works (Nischwitz et al 2017;Mogwasi et al 2018;Mogwasi et al 2019). Based on the herbalist information he most commonly used herbal plants and the protocols used in their preparations were established.…”
Section: Recruitment Of Herbalists and Sampling Of Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive compilation of literature data on the elemental content (macrominerals and trace elements) of medicinal plants and their tisanes, as well as the percentage of element release into infusions and decoctions, is provided by Pohl et al [ 23 ]. For highly relevant elements, such as Cr, Mn, Zn and Cu, it has been shown that the “easily bioavailable fraction” can typically be less than 10% [ 24 ].…”
Section: Discussionmentioning
confidence: 99%